2016
DOI: 10.21475/ajcs.2016.10.09.p7865
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mini core collection from Sri Lankan traditional rice for flowering time variation

Abstract: Sri Lankan traditional rice germplasm (Oryza sativa indica) consists of a wide variety of morphology and days to flowering (DF). The objective of this research was to develop a mini core collection representing the DF variation of the total collection. Three hundred and eighty four rice accessions from 53 Sri Lankan traditional rice varieties were evaluated for morphological and flowering time variation. The experiment was carried at Rice Research and Development Institute, Bathalagoda, Sri Lanka during the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…There are around 500 varieties in the collection while most of the varieties contain more than one accession. Our research group had characterized 755 accessions belonging to several varieties to be used as a breeding resource for manipulation of photoperiod responsiveness, nutrient quality and abiotic stress tolerance in the future: Using 384 accessions belonging to 55 varieties from above, a mini-core collection was developed for flowering time variation (Rathnathunga et al, 2016b). Among the several Sri Lankan rice varieties incorporated in breeding programmes at IRRI, submergence tolerance had been achieved through sub1A-2 gene of Sri Lankan rice James wee (Singh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are around 500 varieties in the collection while most of the varieties contain more than one accession. Our research group had characterized 755 accessions belonging to several varieties to be used as a breeding resource for manipulation of photoperiod responsiveness, nutrient quality and abiotic stress tolerance in the future: Using 384 accessions belonging to 55 varieties from above, a mini-core collection was developed for flowering time variation (Rathnathunga et al, 2016b). Among the several Sri Lankan rice varieties incorporated in breeding programmes at IRRI, submergence tolerance had been achieved through sub1A-2 gene of Sri Lankan rice James wee (Singh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The present study processes the utmost significance as it is the first research project to employ DNA based varietal identification for rice in Sri Lanka. There are more than 2,000 rice accessions including landraces, wild types, and improved cultivars present in the country (Rathnathunga et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Rathnathunga et al (2016) developed a mini core collection of Sri Lankan traditional rice based on wide naturally occurring flowering time variation. In this study, a wide variation in flowering time for photoperiod was detected among selected early maturing accessions: twelve accessions were identified as delayed flowering under inductive SD condition, while fifteen accessions were early flowering under SD condition.…”
Section: Discussionmentioning
confidence: 99%
“…Sri Lanka possesses a wide gene pool of traditional rice with high environmental adaptability through different morphological and physiological characters including plant height, days to flowering (DF), grain shape, pericarp colour and presence of awns (Team of NRC Research Project 12-129, 2014, 2015. Rathnathunga et al (2016) evaluated 384 rice accessions from 53 Sri Lankan traditional rice varieties for morphological and flowering time variation and found that 39 accessions did not flower during the experimental period of 210 days in late short day season. According to PGRC (1999), there were 352 accessions, which flowered at or below 75 days under tested conditions in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%